INFANTILE FEEDING DISTURBANCES AND IMPROVEMENT OPTIONS - V.А. Skvortsova; Т.E. Borovik; М.I. Bakanov; А.V. Migali; Т.N. Stepanova; Е.N. Basargina; L.М. Kuzenkova ("Paediatrician" Publishers LLC, 2011)
Malnutrition is widely spread among infants with severe, especially chronic pathology. Effective treatment of the underlying disease is impossible without adequate diet therapy that includes clinical nutritive products with specially designed composition. Rational feeding positively influences metabolic processes and adds to body mass gain.Key words: malnutrition, hypotrophy, infants, special clinical nutrition, short-life proteins.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (4): 119-125)